2016
DOI: 10.4038/jrrisl.v96i0.1840
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with nitric oxide and seed coat removal improve germination and growth of rubber (<i>Hevea brasiliensis</i>)

Abstract: Studies were carried out on the effect of seed coat removal and nitric oxide (NO) donor sodium nitroprusside (SNP) treatment on germination and growth of seedling and budded plants of rubber (Hevea brasiliensis). Interaction effects were observed between seed coat treatment and SNP treatments for germination time and percentage germination. Decoated seeds germinated earlier and improved synchronicity than intact seeds (with seed coat) and achieved 50% germination within nine days. SNP treatment at all four con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…In this study, the root collar diameter, root diameter, stem length, root length, growth, and the number of leaves were increased when the Q. myrsinifolia seed coat was removed and seeded. Nayanakantha et al [26] reported that rubber (Hevea brasiliensis) seeds were removed from the seed coat and treated with nitric oxide to promote seedlings' germination rate and growth. In addition, it has been reported that the removal of the citrus seed coat promoted the germination rate and the growth of stock 25% more than the intact seed, along with the root induction and root growth [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the root collar diameter, root diameter, stem length, root length, growth, and the number of leaves were increased when the Q. myrsinifolia seed coat was removed and seeded. Nayanakantha et al [26] reported that rubber (Hevea brasiliensis) seeds were removed from the seed coat and treated with nitric oxide to promote seedlings' germination rate and growth. In addition, it has been reported that the removal of the citrus seed coat promoted the germination rate and the growth of stock 25% more than the intact seed, along with the root induction and root growth [25].…”
Section: Discussionmentioning
confidence: 99%
“…The germination rate is one of the important parameters in the rootstock nursery as it determines the number of seedlings and eventually the number of planting material. Some factors influence the germination rate including seed quality [5], storage [6], and treatment before seeding [7]. However, the studies used rubber seeds collected from the field that might have laid on the ground for a varied time after dehisced.…”
Section: Introductionmentioning
confidence: 99%